(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Hematological values at birth encompass broader ranges of normal than at any other time in life, and despite advances in perinatology over the past years, the exact influence of perinatal factors on hematological values in cord blood in normal pregnancy is still unclear. Moreover there was a wide variation and overlap in values between normal and abnormal infants with early symptoms and signs of neonatal sepsis. Objectives: 1. To obtain the values of hematological parameters including complete blood picture, red cell indices, nucleated red blood cells and reticulocyte count in healthy full-term neonate and compare these values in neonates delivered by normal vaginal delivery and those delivered by cesarean section whether as elective or emergendy cesarean section. 2. To evaluate the effect of the gestational age, duration of rupture of membrane, duration of labor, Apgar score and birth weight on some hematological parameters. Subjects, Materials & Methods: A total number of 300 healthy full term newborn were included in this prospective study. They were delivered in Al-Kadhimiya Teaching Hospital / labor room from October 2007 to January 2008. Those newborns were categorized into three groups, including those delivered by normal vaginal delivery (n = 200), by elective cesarean section (n = 80) and by emergency cesarean section (n = 20). From each newborn 5 ml of venous cord blood was aspirated, and the estimation of hematological parameters was performed by Sysmex (automated hematology analyzer). Calibration of the analyzer was performed manually. Additionally the blood film was stained with Leishman,s stain and differential count was done for each slide and reticulocyte count? was done by standard method using brilliant cresyl blue stain. Statistical analysis were done by students t test and correlation test taking P value < 0.05 as the lowest limit of significance. Results: This study revealed that the total white blood cells and absolute neutrophil count were significantly lower in those delivered by elective cesarean section compared to those delivered by normal vaginal delivery (NVD) and emergency cesarean section (CS/L) Moreover the reticulocyte count and nucleated red blood cells of neonates delivered by ECS and NVD were significantly lower than those delivered by CS/L, while the red distribution width (RDW) was significantly lower in those delivered by NVD than those delivered by ECS and CS/L. Whereas the duration of rupture of membrane before delivery, duration of labor, gestational age, birth weight and Apgar score had no influence on cord blood hematological parameters and there was no statistical difference between the three groups. Conclusion: • This study revealed the total WBC count and absolute neutrophil count in those delivered by ECS were significantly lower than those delivered by NVD and CS/L. • The mode of delivery had an influence on RDW in that neonates delivered by NVD had significantly lower RDW than those delivered by ECS and CS/L (p < 0.05). • The mode of delivery had an influence on nucleated red blood cell (NRBC) and reticulocyte count in that neonates delivered by ECS and NVD had significantly lower NRBC and reticulocyte count than those delivered by CS/L (p < 0.05). • The mode of delivery had no statistically significant effect on: lymphocyte, eosinophil, monocyte, RBC, Hb, PCV, MCV, MCH, MCHC, platelet, PDW and MPV. • Duration of labor, duration of rupture of membranes before delivery, gestational age, Apgar scores and birth weight had no influence on cord blood hematological parameters. Key words: Haematolgical parameters; mode of delivery; newborn.